Structure of megabenthic invertebrate communities and ecological function of seagrass ecosystem in Walakiri Waters, Sumba Island, East Nusa Tenggara, Indonesia - RETNO HARTATI; WIDIANINGSIH WIDIANINGSIH; ITA RINIATSIH; FANNY I. GINZEL; ANINDYA WIRASATRIYA; ROBERTUS T. MAHENDRAJAYA; CRISTIANA MANULLANG (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hartati R, Widianingsih, Riniatsih I, Ginzel FI, Wirasatriya A, Mahendrajaya RT, Manullang C. 2025. Structure of megabenthic invertebrate communities and ecological function of seagrass ecosystem in Walakiri Waters, Sumba Island, East Nusa Tenggara, Indonesia. Biodiversitas 26: 5067-5080. This study investigates the diversity and community structure of megabenthic fauna and their ecological relationship with the seagrass ecosystem at Walakiri Beach, Sumba Island, East Nusa Tenggara, Indonesia, a critical coastal habitat. Megabenthos sampling and seagrass assessments were conducted simultaneously along six transect stations, and five resilience indicators (water transparency, species richness, and seagrass and macroalgae/epiphyte coverage) were evaluated to determine the Seagrass Ecological Quality Index (SEQI). A total of 48 megabenthic species were recorded, belonging to five phyla: Mollusca (20 species), Echinodermata (14 species), Porifera (9 species), Arthropoda (4 species), and Chordata (1 species). Mollusca and Echinodermata were the most diverse and abundant groups, reflecting their important ecological roles as consumers, bioturbators, and environmental indicators. The megabenthic community showed high diversity and evenness, with no single species dominating. The seagrass beds consisted of five mixed species, dominated by Thalassia hemprichii, characterized by dense to very dense coverage, forming a suitable habitat that supports diverse megabenthic communities. SEQI results indicated good ecological status, with seagrass functioning effectively as a provider of shelter, food, and nursery grounds. Pearson correlation analysis demonstrated strong positive relationships between megabenthic diversity and evenness, as well as between seagrass cover and dominance, while negative correlations were observed with seagrass diversity and evenness. These results suggest that megabenthic communities flourish in areas dominated by a few seagrass species, particularly T. hemprichii. Although ecological conditions remain favorable, increasing tourism activities may threaten habitat integrity, highlighting the need for sustainable coastal management.